Analysis of the aspiration ratio of double-shrouded probes according to angle of attack and probe scale. Issue 10 (3rd October 2021) - Lim, Jun-Hyung; Hwang, Seok-Ju; Yook, Se-Jin
Abstract: To measure airborne particulate matter concentration over a wide range, a measurement system is mounted on various types of moving vehicles, such as high-speed trains, small drones, and airplanes. Depending on the purpose and range of measurement, the size of the moving vehicle used varies, and the sampling flow rate of the measurement system mounted on the vehicle also varies accordingly. Therefore, an isokinetic sampling inlet with a size suitable for each mobile measurement system must be used. In this study, the aspiration ratio according to various sizes of double-shrouded probes developed to enable representative sampling, including under high-speed flow conditions, was investigated. Considering the various speed ranges of the moving vehicle and relative angle between the moving direction of the vehicle and the surrounding flow direction, the free-stream velocity range around the double-shrouded probe was set to 0–300 km/h and the angle of attack was set to 0–30°. As the angle of attack increased, the aspiration ratio tended to decrease. When the angle of attack is fixed, we found that the aspiration ratio of the double-shrouded probe of various sizes can be made non-dimensional using the square root of the Stokes number. Based on these results, it is expected that the size of the double-shrouded probe suitable for various mobile measurement systems can be easily determined, and accurate measurement of dust concentration is possible through quick prediction of the aspiration ratio according to the velocity of the moving vehicle and angle of attack. Copyright © 2021 American Association for Aerosol Research